(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article shows different principles of politeness in Kazakh nation. The custom that is following through years that our ancestors were carrying is still continuing. If to name, those are the principles of politeness and respect to older and younger people, as well as the hospitality of Kazakh people in wedding parties or in different kinds of meetings with different people, those can be official meeting or just the meeting of good friends and we have tried to show all this kind of politeness in our article. Furthermore, in the article, we have tried to deepen into and clarify the features of politeness of Kazakh’s while greeting. As a result Kazakh people for millenniums accumulated layer of witty, wise sayings. Communicative factors of politeness always dynamic, always implies a connection of tradition to the present mome.